LEVEL OF KNOWLEDGE ABOUT SEXUAL EDUCATION AMONG TEENAGERS AT PPA EMAUS GBI EMAUS WONOSARI PAGU KEDIRI - Rimawati; Indraningrum Fitria (EZRA SCIENCE BULLETIN, 2023)
Teenagers who are not incorporated with accurate information about sexuality can be immersed into sexual intercourse outside marriage, resulted in increasing number of pregnancy outside of marriage as well as sexual transmitted diseases (Suarta 2022). The topic of this study is ”Level of knowledge for sexual education among teenagers in PPA Emaus GBI Emaus at Wonosari, Pagu, Kediri”. The aim of this study is to identify the level of knowledge for sexual education. This study used simple descriptive design using questionnaire as the tool. The study was done at PPA Emaus GBI Emaus Wonosari Kediri with 33 respondents as the sample. The study showed that more than half of the respondents (56,5%) have high level of knowledge, while the rest respondents (43,5%) have moderate level. Therefore, this study recommends to do further study with larger number of respondents.